TiO2 Nanotubes Promote Osteogenic Differentiation Through Regulation of Yap and Piezo1 - Kong, Keyu; Chang, Yongyun; Hu, Yi; Qiao, Hua; Zhao, Chen; Rong, Kewei; Zhang, Pu; Zhang, Jingwei; Zhai, Zanjing; Li, Huiwu (Frontiers in Bioengineering and Biotechnology, 2022)
Surface modification of titanium has been a hot topic to promote bone integration between implants and bone tissue. Titanium dioxide nanotubes fabricated on the surface of titanium by anodic oxidation have been a mature scheme that has shown to promote osteogenesis in vitro. However, mechanisms behind such a phenomenon remain elusive. In this study, we verified the enhanced osteogenesis of BMSCs on nanotopographic titanium in vitro and proved its effect in vivo by constructing a bone defect model in rats. In addition, the role of the mechanosensitive molecule Yap is studied in this research by the application of the Yap inhibitor verteporfin and knockdown/overexpression of Yap in MC3T3-E1 cells. Piezo1 is a mechanosensitive ion channel discovered in recent years and found to be elemental in bone metabolism. In our study, we preliminarily figured out the regulatory relationship between Yap and Piezo1 and proved Piezo1 as a downstream effector of Yap and nanotube-stimulated osteogenesis. In conclusion, this research proved that nanotopography promoted osteogenesis by increasing nuclear localization of Yap and activating the expression of Piezo1 downstream.